2003
DOI: 10.1042/bj20030175
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic glucocorticoid receptor interaction with nuclear factor-kappaB proteins in rat liver cells

Abstract: The glucocorticoid receptor (GR) acts as an anti-inflammatory factor. To a large extent, this activity is exerted by the interference of pro-inflammatory nuclear factor kappa B (NF-kappa B) activity. In their respective inactive forms, both GR and NF-kappa B reside in the cytoplasm and translocate to the nucleus on relevant stimulation. Previously, p65, a component of the NF-kappa B complex, and GR have been shown to interact physically in vitro, and the interaction is assumed to take place in the nucleus of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 26 publications
2
30
1
3
Order By: Relevance
“…Contrary to current beliefs, we found that p65, p50 and I-B were co-immunopurifying with cytosolic, nonliganded, non-activated GR (Widén et al 2003). The current understanding of GR and NF-B interaction favours the model that glucocorticoids induce the GR-NF-B interaction and that this interaction would be one of two possible mechanisms for how glucocorticoids counteract inflammation mediated by NF-B.…”
Section: Studies Of Gr and Nf-b Proteinscontrasting
confidence: 53%
See 1 more Smart Citation
“…Contrary to current beliefs, we found that p65, p50 and I-B were co-immunopurifying with cytosolic, nonliganded, non-activated GR (Widén et al 2003). The current understanding of GR and NF-B interaction favours the model that glucocorticoids induce the GR-NF-B interaction and that this interaction would be one of two possible mechanisms for how glucocorticoids counteract inflammation mediated by NF-B.…”
Section: Studies Of Gr and Nf-b Proteinscontrasting
confidence: 53%
“…Several of the interacting proteins that we have studied have, in turn, been reported to interact with other proteins important for signal transduction. Based on this information we have tested whether the interaction with GR also allows for interaction with previously described secondary interaction partners (Widén et al 2000, Widén et al 2003 and have sometimes found this to be the case (see below).…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, these interactions can occur even in the absence of glucocorticoids or of an inflammatory signal (Wide´n et al, 2003) (Figure 1). Furthermore, the NF-kB-IkB complex had already been found to shuttle between the cytoplasm and the nucleus in the absence of signal (Johnson et al, 1999;Carlotti et al, 2000;Ghosh and Karin, 2002).…”
Section: Cytoplasmic Modelsmentioning
confidence: 99%
“…Glutathione S-transferase (GST) and GST-RHD fusion proteins were expressed in Escherichia coli strain DH5␣ (Invitrogen) and were purified as described (29). Briefly, a 50-ml culture of the expression vector was stimulated with 0.5 mM isopropyl-1-thio-␤-D-galactopyranoside (Sigma) and grown for 3 h. The bacteria were then pelleted and resuspended in NETN buffer (20 mM Tris, pH 8.0, 100 mM NaCl, 1 mM EDTA, 0.01% Nonidet P-40) supplemented with protease inhibitors ("Complete"; Roche Applied Science).…”
Section: Interaction Of P65-rhd and The Glucocorticoid Receptor In VImentioning
confidence: 99%